Esophageal Squamous Cell Carcinoma Masquerading as Achalasia: A Case Report on Diagnostic Pitfalls and Therapeutic Strategies - Renata Timoty Pasaribu; I Gde Ardika Nuaba; I Ketut Suanda; Ida Ayu Alit Widiantari; I Wayan Lolik Lesmana (HM Publisher, 2025)
Esophageal squamous cell carcinoma (SCC) is an aggressive malignancy often diagnosed at an advanced stage, leading to a poor prognosis. Its initial symptoms can be nonspecific, occasionally mimicking benign esophageal disorders such as achalasia, thereby posing significant diagnostic challenges. This report details such a case, emphasizing the diagnostic pitfalls and discussing therapeutic approaches. A 43-year-old male presented with a 5-month history of progressive dysphagia and odynophagia, initially suspected to be achalasia. Clinical findings, including significant weight loss and specific laboratory abnormalities, are detailed. Esophagogastroduodenoscopy revealed an obstructing tumor, confirmed as esophageal SCC by biopsy. Staging investigations, including Multi-Slice Computed Tomography (MSCT), characterized the disease as Stage IVA (T4N1M0). The patient underwent feeding gastrostomy for nutritional support and commenced systemic chemotherapy with docetaxel, carboplatin, and cetuximab. The treatment course and initial follow-up are described. In conclusion, this case underscores the critical importance of maintaining a high index of suspicion for malignancy in patients presenting with symptoms suggestive of achalasia, especially if accompanied by atypical features or risk factors. A meticulous and timely diagnostic evaluation, incorporating early endoscopy and biopsy, is paramount for accurate diagnosis and staging. Multidisciplinary management, including robust nutritional support and carefully selected systemic therapy, remains central to addressing advanced esophageal SCC.